A Review of Cyber Security Assessment (CSA) for Industrial Control Systems (ICS) and Their Impact on the Availability of the ICS Operation - Bonandir N.A.; Jamil N.; Nawawi M.N.A.; Jidin R.; Rusli M.E.; Yan L.K.; Maudau L.L.A.D. (IOP Publishing Ltd, 2023)
Control systems; Security of data; Cyber security; Industrial control systems; Industrial operations; Regular operations; Security aspects; Security assessment; System availability; Wireless connectivities; Availability